2019
DOI: 10.1308/rcsann.2018.0168
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of urgent suspicion of head and neck cancer referrals in Glasgow

Abstract: Introduction Primary care patients with a suspected head and neck cancer are referred through the urgent suspicion of cancer referral pathway. Rates of cancer detection through this pathway are low. Evidence surrounding the pathway of these patients is lacking. This study aimed to determine the outcome of urgent suspicion of cancer referrals for head and neck cancer. Methods and methods All head and neck cancer urgent suspicion of cancer referrals in NHS Greater Glasgow and Clyde between June 2015 and May 2016… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 2 publications
4
27
0
Order By: Relevance
“…Considering clinical outcomes, the cancer diagnosis rate of 12% in the RDC was comparable with conversion rates in many site-specific cancer pathways. Urgent suspected cancer pathway conversion rates were reported to be between a median of 8.0% and 17.0%, 20 and to have a mean of 11.8%, 21 depending on the use of urgent pathways, referral rates, and cancer type. Also, a recent systematic review and metaanalysis of fast-track diagnosis of colorectal cancer found a cancer detection rate of 7.7% (confidence interval = 6.9% to 8.5%).…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Considering clinical outcomes, the cancer diagnosis rate of 12% in the RDC was comparable with conversion rates in many site-specific cancer pathways. Urgent suspected cancer pathway conversion rates were reported to be between a median of 8.0% and 17.0%, 20 and to have a mean of 11.8%, 21 depending on the use of urgent pathways, referral rates, and cancer type. Also, a recent systematic review and metaanalysis of fast-track diagnosis of colorectal cancer found a cancer detection rate of 7.7% (confidence interval = 6.9% to 8.5%).…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…The overall cancer incidence of 5.6% identified in this study is consistent with rates reported in the literature and by national data sets, which vary between 3.6% and 11.8%, and it also corresponds with a national trend toward lower incidence rates in this population over time as the number of suspected cancer referrals to secondary care increases. 9,17,[22][23][24] As the number of referrals increases, risk stratification may become even more important for Cancer Month 0, 2021 appropriate hospital resource allocation and the identification of cancers, which represent a diminishing proportion of the referrals coming in. However, burdening primary care physicians with collecting and recording symptom data for risk stratification is unlikely to be appropriate.…”
mentioning
confidence: 99%
“…This is in keeping with the audits and reviews from other sites, further questioning the 2ww pathway symptom guidelines. 7,8,9 There is no dispute in the necessity of patients being seen promptly for suspected HNCs. However, this does highlight the high sensitivity and low specificity of the 2ww as a screening tool.…”
Section: Discussionmentioning
confidence: 99%
“…A recent audit from a head and neck cancer unit in Glasgow showed that, in one year, 7.6% of patients referred under the 2ww pathway were positive for a primary HNC. 7 Pindolia et al showed that 96% of the 2ww referrals in a major London head and neck centre were nonmalignant, instead resulting in diagnoses such as oral lichen planus and recurrent aphthous ulceration (47% and 14%, respectively). 8 This questions whether the 2ww pathway is being overused by referring practitioners.…”
Section: Introductionmentioning
confidence: 99%